2009
DOI: 10.1152/ajpcell.00311.2009
|View full text |Cite
|
Sign up to set email alerts
|

A large-conductance (BK) potassium channel subtype affects both growth and mineralization of human osteoblasts

Abstract: The pharmacology of the large-conductance K(+) (BK) channel in human osteoblasts is not well defined, and its role in bone is speculative. Here we assess BK channel properties in MG63 cells and primary human osteoblasts and determine whether pharmacological modulation affects cell function. We used RT-PCR and patch-clamp methods to determine the expression of BK channel subunits and cell number assays in the absence and presence of BK channel modulators. RT-PCR showed the presence of KCNMA1, KCNMB1, KCNMB2, KC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 44 publications
2
35
1
1
Order By: Relevance
“…Zhou et al, (2008) demonstrated that BK channels were inhibited by Gbg-protein and we previously reported that BK channels were expressed in SaM-1 cells (Hirukawa et al, 2008). However, BK channels are inhibited by TEA and activated by [Ca 2+ ]i elevation (Henney et al, 2009;Lee and Cui, 2010). The inhibition of the current by noradrenaline was seen at cell potentials below -60 mV, and further inhibition was seen over 0 mV ( Figure 1C).…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…Zhou et al, (2008) demonstrated that BK channels were inhibited by Gbg-protein and we previously reported that BK channels were expressed in SaM-1 cells (Hirukawa et al, 2008). However, BK channels are inhibited by TEA and activated by [Ca 2+ ]i elevation (Henney et al, 2009;Lee and Cui, 2010). The inhibition of the current by noradrenaline was seen at cell potentials below -60 mV, and further inhibition was seen over 0 mV ( Figure 1C).…”
Section: Discussionsupporting
confidence: 54%
“…A number of studies have demonstrated that membrane potential and cell proliferation capacity were regulated by activities of potassium channels in several types of cells including osteoblasts (Pardo et al, 2005;Liebau et al, 2006;Henney et al, 2009;Jang et al, 2011). Adequate inhibition of potassium channels is thought to cause membrane depolarization and activate voltage-dependent calcium channels, leading to cell proliferation (Burg et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…关于异海松酸的生物活性研究 报道较多的是其活化大型钙离子激活的钾离子(BK)通 道的活性 [1,2] . 进一步研究表明, 异海松酸作为 BK 通道 的活化剂可以调控初级成骨细胞的生长和矿化 [3] , 并降 低小鼠听觉神经网络自发活动的多动症和改善患阿尔 茨海默病小鼠的认知功能, 从而对神经活性多动症和阿 尔茨海默病具有潜在的治疗效果 [4,5] . 其次, 异海松酸对 结核病毒具有显著的疗效 [6] , 并对爱博斯坦巴尔病毒 也显示出抑制效果 [7] .…”
Section: 酰基-N′-(3-甲基苯基)硫脲(3c)和 N-异海松酰胺基-n'-(4-氟苯基)硫脲(6b)对癌细胞的抑制率达到unclassified